PENGELOLAAN LINGKUNGAN BELAJAR BERBASIS SENTRA BAHAN ALAM DALAM MENGEMBANGKAN KARAKTER MANDIRI ANAK - Kusayang, Titin; Novalia, Rifyal; Yuliasti, Tatia; Nurliza; Afrianel, Sri (Bunayya, 2026)
The management of the learning environment in the natural materials center is important to examine, as studies positioning it as a pedagogical strategy for developing independent character in early childhood remain limited. This study aimed to describe the management of a learning environment based on the natural materials center and its contribution to children’s independent character at Lukmanul Hakim Kindergarten. This research employed a descriptive qualitative approach and involved one principal, one natural materials center teacher, and 13 children aged 5–6 years as research subjects. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through the stages of data reduction, data display, and conclusion drawing. The findings revealed that learning management in the natural materials center was implemented through four main scaffolding stages: environmental scaffolding for play, pre-play scaffolding, during-play scaffolding, and post-play scaffolding. These four stages contributed to the development of children’s independent character, as reflected in their ability to choose materials, use tools, attempt to complete activities, ask questions when encountering difficulties, and tidy up tools and materials after use. These findings reinforce the understanding that the natural materials center is not merely a play space but also a learning environment that supports children’s independence through concrete experiences, habituation, and opportunities to act independently.